The state of citizen participation in America - Schachter, Hindy Lauer; Yang, Kaifeng (A volume in international civic engagement, 2012)
This book provides a state-of-the-art assessment of citizen participation practice and research in the United States. With contributions from a stellar group of scholars, it provides readers an overview of a field at the heart of democratic governance. Individual chapters trace shifts in participation philosophy and policy, examine trends at different government levels, analyze technology/participation interactions, identify the participation experiences of minority populations, and explore the impact of voluntary organizations on this topic. A five-chapter section illustrates innovative cases. Another section explores the role of various methodologies in advancing participation research.The scope, depth, and timeliness of the coverage fills two voids in the public administration literature. First, the book provides a unique collection of articles for graduate courses in citizen participation and democratic governance. The volume also offers an excellent compendium for researchers who are at the frontline of participation research and practice.